Impact of COVID-19 pandemic on child abuse and neglect: A cross-sectional study in a French Child Advocacy Center. (August 2022) - Massiot, L.; Launay, E.; Fleury, J.; Poullaouec, C.; Lemesle, M.; Guen, C. Gras-le; Vabres, N.
Abstract: Objective: This study aimed to describe the impact of the first COVID-19 lockdown in France on the activity of a Child Advocacy Center. Methods: This cross-sectional, observational study included all children involved in the activity of the CAC during the first lockdown, from March 16 to May 10, 2020 and the next 3 months and the corresponding periods in 2018 and 2019. Cases were considered severe when a hospitalization, social alert and/or judicial report to the prosecutor was decided. Results: Data for 1583 children were analyzed. During the lockdown, the global center activity decreased with 26.4 consultations per 100.000 children in 2018, 46 in 2019 and 20.7 in 2020 ( p  < 0.001). Judicial activity decreased (forensic examinations and child forensic interview recordings), whereas assessment consultations increased. Cases were more severe during the lockdown than in 2019 and 2018 (12.3, 9.4 and 6.04/100.000 children, respectively, p  < 0.0001). The global activity of the center increased in the 3 months after the lockdown as compared with during the lockdown (38.2/100.000 versus 20.7/100.000, respectively, p  < 0.001) but did not differ from activity in 2018 and 2019. Severe cases were more frequent in the 3 months after the lockdown than the previous years (13.7/100.000 in 2020, 9.62 in 2019 and 8.17 in 2018, p  = 0.0002). Conclusion: The CAC activity decreased during the lockdown in France but the increase in incidence of severe abuse cases during the lockdown and the next 3 months confirm the need for optimal screening, care and support of child abuse and neglect victims even in the context of health crisis. Highlights: The first lockdown was associated with a decrease in activity of the child advocacy center. The decrease in activity was due to a decrease in forensic examinations and child forensic interview recordings. Children were more severely abused compared with the 2 previous years. These results highlight the consequences of the lockdown on need of care and its availability for children. These results call for increased vigilance of the risk of child abuse during periods of crisis.